Kritik Nalar Agama dalam Film Tanda Tanya (‘?’) - Basri, Huda Hasan (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2014)
This article deals with the meaning of religious pluralism in the cinema Film Tanda Tanya (Movie of Question Mark'?'). Using a semiotic approach and genre analysis, this paper argues that the film directed and produced by Hanung Bramantyo can be categorized as a critical-reconstructive religious genre offering social critique on the communication of religious life in Indonesia, which is often tinged with terror. In addition, the film also seeks to reconstruct religious reasons in a moderate, plural, and tolerant way, so that religious communities can keep themselves away from the trap of religious fundamentalism, which often trigger sectarian conflicts.Keywords: Movie critique, religious reason, genre analysis, semiotic, religious pluralism.———————————————————————-Artikel ini mendiskusikan makna pluralisme agama dalam film Tanda Tanya “?”. Melalui pendekatan semiotik dan analisis genre, tulisan ini berpendapat bahwa film besutan Hanung Bramantyo ini, termasuk genre religi kritis-rekonstruktif, yang menawarkan kritik sosial atas komunikasi kehidupan beragama di Indonesia yang kerap diwarnai dengan aksi terror. Selain itu, film ini juga berupaya merekonstruksi nalar agama masyarakat yang skriptural-tekstualis agar terlepas dari jebakan fundamentalisme agama, yang kerap memicu terjadinya konflik antar umat beragama.Kata Kunci: kritik nalar agama, makna relasional, analisis genre, semiotik, pluralism agama